Solid tumor metastases to the pancreas diagnosed by FNA: A single‐institution experience and review of the literature. Issue 6 (30th March 2015) - Smith, Amber L.; Odronic, Shelley I.; Springer, Bridgette S.; Reynolds, Jordan P.
<x xml:space="preserve">Abstract</x> BACKGROUND Pancreatic fine‐needle aspiration (FNA) is useful for diagnosing pancreatic masses. This article describes the experience of a single institution with metastases to the pancreas sampled by FNA and provides a review of the literature. METHODS Medical records were retrospectively searched for pancreatic FNA that showed metastatic disease. Data were gathered for the tumor size, focality, and time period between the primary tumor and the metastasis. A literature search using PubMed was performed. RESULTS Pancreatic FNA was performed 2327 times in 14 years at the authors' institution. Twenty‐two cases showed metastatic disease. The average size of the metastatic lesions in their greatest dimension was 3.7 cm (range, 1.5‐6.5 cm). The majority of the tumors were unifocal (16 of 22 or 73%). A rapid onsite adequacy evaluation was performed for 13 patients (4 were diagnostic of metastasis, 3 were positive for malignant cells, 6 were atypical, and none were negative). There were 14 renal cell carcinomas, 2 colonic adenocarcinomas, 1 urothelial carcinoma, 1 non–small cell lung carcinoma, 1 ovarian serous carcinoma, 1 prostatic adenocarcinoma, 1 papillary thyroid carcinoma, and 1 mesenchymal chondrosarcoma. The median time between the diagnosis of the primary tumor and the initial pancreatic metastasis was 9 years (range, concurrent diagnosis to 21 years). A literature review yielded 12 case series with a variety of metastases to the pancreas diagnosed by FNA and surgical pathology specimens. CONCLUSIONS In agreement with prior series, the most common metastasis to the pancreas was renal cell carcinoma. A variety of other primary malignancies were also documented in this study and in the literature. Also, this article reports the first case of metastatic mesenchymal chondrosarcoma to the pancreas diagnosed by FNA. Cancer (Cancer Cytopathol) 2015;123:347–55. © 2015 American Cancer Society.